Molecular Reconstruction of an Old Pedigree of Diploid and Triploid Hydrangea macrophylla Genotypes - Hempel, Peter; Hohe, Annette; Tränkner, Conny (Frontiers in Plant Science, 2018)
The ornamental crop species Hydrangea macrophylla exhibits diploid and triploid levels of ploidy and develops lacecap (wild type) or mophead inflorescences. In order to characterize a H. macrophylla germplasm collection, we determined the inflorescence type and the 2C DNA content of 120 plants representing 43 cultivars. We identified 78 putative diploid and 39 putative triploid plants by flow cytometry. 69 out of 98 flowering plants produced lacecap inflorescences, whereas 29 plants developed mophead inflorescences. Surprisingly, 12 cultivars included diploid as well as triploid plants, while 5 cultivars contained plants with different inflorescence types. We genotyped this germplasm collection using 12 SSR markers that detected 2 to 7 alleles per marker, and identified 51 different alleles in this collection. We detected 62 distinct fingerprints, revealing a higher genetic variation than the number of cultivars suggested. Only one genotype per cultivar is expected due to the vegetative propagation of Hydrangea cultivars; however we identified 25 cultivars containing 2 to 4 different genotypes. These different genotypes varied with regard to DNA content and inflorescence type. We found 36% of these plants were mislabeled, with diploid and triploid plants with the same cultivar name were exclusively mix-ups. Based on the “Wädenswil” pedigree, which includes 31 of these tested cultivars, we predicted cultivar-specific fingerprints and identified at least 21 out of 31 cultivars by SSR marker-based reconstruction of the “Wädenswil” pedigree. Furthermore, we detected 4 putative interploid crosses between diploid and triploid plants in this pedigree. These interploid crosses resulted in diploid or/and triploid offspring, suggesting that crosses with triploids were successfully applied in breeding of H. macrophylla.